An Analisys Of The Heating Value Of Briquettes Made From A Mixture Of Rice Husk and Tea Dregs using Tapioca Adhesive - Hendra Irawan; Hendri Nurdin; Ambyar Ambyar; Rahmat Azis Nabawi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
Increased energy consumption and lack of public knowledge to utilize rice husks and tea pulp as the most untapped briquette. The purpose of this research is to obtain a Calor value produced by rice husk briquette and tea pulp to be used as a briquette as an alternative fuel.. The results of the heat value test conducted using the Bomb calorimeter test tool showed optimum heat value in the variation of the 80% rice husk mixture and tea pulp and 20% tapioca adhesive, the value of the resulting heat of 11,638,112 kj/kg. This shows that the rice husk briquette and tea pulp with a mixture of comparison of 80% mixture of raw materials with 20% tapioca as higher glues produce a Calor value than 3 other variations. Based on the process that has been done shows that rice husk and tea pulp are potentially an alternative fuel.briquette and testing showed that rice husk and tea pulp could be potentially alternative fuel Konsumsi energi yang semakin meningkat dan kurangnya pengetahuan masyarakat dalam memanfaatkan sekam padi dan ampas teh sebagai briket yang belum dimanfaatkan secara maksimal. Tujuan penelitian ini adalah untuk mendapatkan nilai kalor yang dihasilkan briket sekam padi dan ampas teh untuk dijadikan briket sebagai bahan bakar alternatif.. Hasil pengujian nilai kalor yang dilakukan mengunakan alat bomb calorimeter test menunjukan nilai kalor yang optimum pada variasi 80% campuran sekam padi dan ampas teh dan 20% perekat tapioka, nilai kalor yang dihasilkan sebesar 11638.112 kj/kg. Hal ini menunjukan bahwa briket sekam padi dan ampas teh dengan perbandingan campuran 80% campuran bahan baku dengan 20% tapioka sebagai perekatnya lebih tinggi menghasilkan nilai kalor dari 3 variasi lainnya. Berdasarkan proses yang telah dilakukan menunjukan bahwa sekam padi dan ampas teh berpotensi sebagai bahan bakar alternatif.